2012
DOI: 10.4028/www.scientific.net/msf.706-709.2502
|View full text |Cite
|
Sign up to set email alerts
|

Recrystallization in HR3C Austenitic Heat Resistant Steel

Abstract: In the present study, the recrystallization and grain growth behavior of HR3C austenitic heat resistant steel were studied by scanning electron microscopy and electron backscatter diffraction (SEM/EBSD). The HR3C steel was forged into a plate of 12mm in thickness and then solution treated at 1150-1250°C followed by an annealing treatment at 650-1050°C for 1h. The results show that the recrystalization occurs during the annealing treatment when the steel is solution-treated at 1150°C. Increasing the solution te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Iseda et al (2007) concluded that the sufficient toughness and microstructural stability can be maintained after the long term aging of HR3C steel at 500-750 • C. Peng et al (2010) found out that the M 23 C 6 precipitating on grain boundaries can result in the reduction of the impact toughness after aging for various time at 700 • C. The reasonable hot working process can be controlled to obtain high product rate and desired microstructures. Yin et al (2012) revealed a distinctive phenomenon that the recrystallization would occur during the annealing treatment after HR3C steel was solution-treated at 1150 • C. The dislocation of high density remained in the matrix of the steel is responsible for the driving force of recrystallization. Yanushkevich et al (2015) described grain refinement of an S304H-type steel during multiple rolling at temperatures of 500 • C to 1000 • C and found that rolling up to the strain of 2 can obtain the ultrafine-grained microstructure.…”
Section: Introductionmentioning
confidence: 96%
“…Iseda et al (2007) concluded that the sufficient toughness and microstructural stability can be maintained after the long term aging of HR3C steel at 500-750 • C. Peng et al (2010) found out that the M 23 C 6 precipitating on grain boundaries can result in the reduction of the impact toughness after aging for various time at 700 • C. The reasonable hot working process can be controlled to obtain high product rate and desired microstructures. Yin et al (2012) revealed a distinctive phenomenon that the recrystallization would occur during the annealing treatment after HR3C steel was solution-treated at 1150 • C. The dislocation of high density remained in the matrix of the steel is responsible for the driving force of recrystallization. Yanushkevich et al (2015) described grain refinement of an S304H-type steel during multiple rolling at temperatures of 500 • C to 1000 • C and found that rolling up to the strain of 2 can obtain the ultrafine-grained microstructure.…”
Section: Introductionmentioning
confidence: 96%